Factors Related To Patient Adherence To Anti Tuberculosis Drug Treatment At The Mekar Jaya Health Center - Yeni Indriyani; Sutriyati Sutriyati; Rima Ernia; Muslimin Muslimin (Science Midwifery, 2021)
Regular administration of Anti Tuberculosis Drug is one of key success of tuberculosis treatmen. Discontinuing treatment, has resulted a double immune and Multu Drug Resistant (MDR) in pulmonary tuberculosis bacterias. The purpose of this study was to determine the effect of Attitude, Distance and Family Support on adherence to anti Tuberculosis Treatment. Subject and Method: This study was a cross-sectional study carried out in working area Mekar Jaya Health Center. A total sample 65 patents who diagnosed TB which cunducted in April 2021. The dependent variable was adherence to Anti Tuberculosis Drug. The independent variables were Attitude,Distance and family support. Result: The findings revealed that 61.5 % of respondents did not comply with treatment, while 38.5 %. The bivariate test results attitude was possitively associated (p-value 0.009; OR; 3.946 CI (1.364-11.416), distance p-value 0.002, OR; 5.333 CI (1.801-15.797), and family support with p-value 0.003, OR 5.091 CI (1.684-15.390) To concluded, attitude, distance and family support are associated with patient’s adherence to anti tuberculosis drug treatment.